Evaluating Current Increased Price and Fattening Cost of BX Cattle with ESCAS Cost on Slaughtered Cattle Price and their Welfare - Puradireja Rino Hadiwijaya; Daud Rivianda Andre; Ramdani Diky (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
The Australian Brahman Cross (BX) cattle industry is very modern. They have created a comprehensive system guided by the principles of animal welfare. The importation of BX cattle by companies in Indonesia will be bound by the Exporter Supply Chain Assurance System (ESCAS) regulations. This study aimed to evaluate the current increased price and fattening cost of feeder Brahman Cross (BX) cattle along with ESCAS additional cost on the price of slaughtered cattle and their welfare. Based on the results, the animal welfare assessment in the feedlot for 120 days were considered good, with the average value in the first month 86.40%, then in the second month 88.50%, in the third month 92.14%, and the fourth month 94.29%. Based on the calculations result of the Activity Based Costing (ABC) method in each supply chain, it is known that procurement costs, including the purchase of feeders, contributed to 94,0% of the total costs, while other costs were handling costs 2.70%, cost of ESCAS 1.56%, selling cost 1.52%, and the lowest, maintenance cost 0.24%. Therefore, to fatten Australian BX cattle, special strategies are needed, such as: optimizing stock in the feedlot; efficiency cost in feed ingredients without reducing quality; applying animal welfare rules to minimize handling costs and selecting vendors who want the lower price in providing ESCAS support facilities and establishing regular maintenance of the ESCAS supporting tools.